2006
DOI: 10.2139/ssrn.898181
|View full text |Cite
|
Sign up to set email alerts
|

Do Stock Market Investors Understand the Risk Sentiment of Corporate Annual Reports?

Abstract: , and the workshop participants at the University of Michigan for their comments. All errors remain mine. AbstractI test the stock market efficiency with respect to the information in the texts of annual reports. More specifically, I examine the implications of corporate annual reports' risk sentiment for future earnings and stock returns. I measure the risk sentiment of annual reports by counting the frequency of words related to risk or uncertainty in the 10-K filings. I find that an increase in risk sentime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
165
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(184 citation statements)
references
References 14 publications
13
165
3
3
Order By: Relevance
“…For example, Li (2006) counts the frequency of the word stems "risk" and "uncertain" over a sample period that pre-dates the risk factor disclosure mandate, 1993 to 2004, and finds that an increase in the risk sentiment of annual reports is associated with lower future earnings and equity returns. Kravet and Muslu (2013) counts the number of sentences containing risk-related keywords in corporate annual reports over a sample period that spans both the PSLRA safe harbor and the risk factor disclosure mandate, 1994 to 2007, and finds that increases in this measure are associated with increased stock return volatility and trading volume around the 10-K filing date, as well increased volatility of analyst forecast revisions.…”
Section: Risk Disclosuresmentioning
confidence: 99%
“…For example, Li (2006) counts the frequency of the word stems "risk" and "uncertain" over a sample period that pre-dates the risk factor disclosure mandate, 1993 to 2004, and finds that an increase in the risk sentiment of annual reports is associated with lower future earnings and equity returns. Kravet and Muslu (2013) counts the number of sentences containing risk-related keywords in corporate annual reports over a sample period that spans both the PSLRA safe harbor and the risk factor disclosure mandate, 1994 to 2007, and finds that increases in this measure are associated with increased stock return volatility and trading volume around the 10-K filing date, as well increased volatility of analyst forecast revisions.…”
Section: Risk Disclosuresmentioning
confidence: 99%
“…stories and disclosures seem to decrease the cost of capital and negative disclosures increase it. 10 Related to this line of enquiry, is the study by Li (April, 2006) This goes against the intuition that higher pessimism should lead to lower returns, or equivalently, lower risk, suggesting that the pessimism factor captured by negative words may be distinct from risk. This is further corroborated by the fact that the effects of pessimism seem to be temporary and future stock returns reverse.…”
Section: Prior Researchmentioning
confidence: 99%
“…Some studies further reported that disclosure decisions are associated with management incentives (Merkley, 2014;Kravet & Muslu, 2013;Davis, Piger, & Sedor, 2012;Price, Doran, Peterson, & Bliss, 2012;Loughran & McDonald, 2011;Henry, 2008;Li, 2006). This study differs from above-mentioned studies in attempting to examine the relationship between the disclosure of MI and CSR companies by examining whether CSR companies are more likely to disclosure the MI, because CSR matters to the market, and assessments of CSR can potentially provide useful and timely information to investors.…”
Section: Literature Reviewmentioning
confidence: 92%
“…These findings indicate that CSR is among the most important reputation assets of a company and that market participants perceive such disclosure as responsible behavior. Third, previous studies (Ertimur, Sletten, & Sunder, 2011;Brown, Hillegeist, & Lo, 2009;Li, 2006Li, , 2008Bloomfield, 2008) found that disclosures are often associated with uncertainty in a firm's operations. This study takes the examination further by demonstrating that the disclosure of MI by CSR companies may reflect in the quality of financial reporting.…”
Section: Introductionmentioning
confidence: 93%